Strategy Plan and Policy Model of Public Transport in Saudi Arabia - Jamal Eid Abdulaal; Bader Alanazi; Herika Muhamad Taki (Politeknik Negeri Batam, 2023)
GDP of Saudi Arabia has increased from 1 billion US dollar in 1972 to more than 300 billion US dollar in 2011. The increase in population from 10 million in 1950 to 28 million in 2010, urbanization represent about 80%. the country consume about 20-25% of it's own oil production about 2.5 million per/daily. This shows that the Saudi policy have given incentive to cars user for longtime and has done little to manage demand or support public transport. The main objective of this paper is place the Saudi model in public transport in the international context and to draw an international prospective of public transport policy and the rational of government intervention in transport sector. The study gives classification models which characterize the industries and form of intervention. Further more the study highlight some of the approaches which adopted by both developed and developing industry at specific time. The Methods and models use vary from one country and this study had classified intervention in transport sector in five models which are such as models of ownership, regulation, competition, finance system and private public partnership model. In 2011 Saudi Arabia has introduce it First National Transport Strategy, which have adopted many objectives among the most is, to improve efficiency of transport sector, module environmental impact of transport sector, improves safety facilitate the movement of peoples and goods to improve economic activity (MOT 2011). This state shows that no clear objectives to improve public transport policy.